2018
DOI: 10.7150/jca.22915
|View full text |Cite
|
Sign up to set email alerts
|

IDH1/2 Mutations Predict Shorter Survival in Chondrosarcoma

Abstract: Background. Recent studies have shown that isocitrate dehydrogenase 1/2 (IDH1/2)- activating mutations occur in a variety of cancers, including acute myeloid leukaemia, gliomas, and chondrosarcomas (CHS)s. The effect of IDH1/2 mutation on overall survival (OS) has not been reported in CHS. The aim of our study was to assess the prevalence of known cancer-related gene mutations in CHS, as well as their prognostic role in patient survival.Methods. DNA from FFPE samples of 80 patients (F:M- 1:1.3; mean age: 58 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 51 publications
(58 reference statements)
3
68
2
2
Order By: Relevance
“…Genetically, chondrosarcomas of primary and secondary types are characterized by mutations in the isocitrate dehydrogenase isoforms IDH1 and IDH2, which have been detected in approximately 50% to 60% of primary and secondary central chondrosarcomas. 71,72 Peripheral chondrosarcomas appear to show similar EXT1 and EXT2 aberrations to solitary and hereditary osteochondromas. 73 The genetic underpinnings mediating the transformation from benign cartilaginous lesions to malignant lesions are not entirely elucidated; however, complex karyotypic abnormalities, mutations in TP53, and defects in the RB1 pathway have been described in these lesions as they transform into higher-grade chondrosarcomas.…”
Section: Low-grade Chondrosarcoma and Atypicalmentioning
confidence: 96%
“…Genetically, chondrosarcomas of primary and secondary types are characterized by mutations in the isocitrate dehydrogenase isoforms IDH1 and IDH2, which have been detected in approximately 50% to 60% of primary and secondary central chondrosarcomas. 71,72 Peripheral chondrosarcomas appear to show similar EXT1 and EXT2 aberrations to solitary and hereditary osteochondromas. 73 The genetic underpinnings mediating the transformation from benign cartilaginous lesions to malignant lesions are not entirely elucidated; however, complex karyotypic abnormalities, mutations in TP53, and defects in the RB1 pathway have been described in these lesions as they transform into higher-grade chondrosarcomas.…”
Section: Low-grade Chondrosarcoma and Atypicalmentioning
confidence: 96%
“…Long-term outcomes did not differ in a series of patients with chondrosarcomas harbouring IDH mutations when compared to IDH wild-type chondrosarcoma [65]. In contrast, IDH1 and IDH2 mutant chondrosarcoma had worse outcomes relative to IDH wild-type chondrosarcoma in another study reported by Lugowksa et al [66]. The authors of both studies performed correlation with the tumour grade; however, the histological subtype was not investigated.…”
Section: Idh Mutations In Chondrosarcoma-histopathological and Clinicmentioning
confidence: 90%
“…Hotspot mutations are present at the IDH1 p.Arg132 and the IDH2 p.Arg172 positions, the former being the most frequent. Mutations at the IDH1 p.Arg140 position have also been reported [67]. Grade 2 and 3 central chondrosarcomas are intermediate-and high-grade malignant tumors, respectively.…”
Section: Central Chondrosarcomasmentioning
confidence: 95%
“…Grade 2 and 3 central chondrosarcomas, including dedifferentiated chondrosarcomas are also characterized by complex karyotypes with aneuploidy [39,71]. Other genetic alterations described in the literature are alterations of the RB1 pathway (86% of cases) with a loss of p16 and an overexpression and/or amplification of CDK4, a mutation of TP53 (in up to 59% of the cases) [72] and mutations in COL2A1 (in 45% of cases) [73,74], and also mutations in YEATS2 (12%), EGFR (19%), NRAS (12%), and IHH signaling (18%) [67,74,75]. In about 75% of cases, CDKN2A copy number variations are present.…”
Section: Central Chondrosarcomasmentioning
confidence: 99%